2019
DOI: 10.1111/1365-2745.13263
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic factors and initial conditions influence successional trajectories of early regenerating tropical dry forests

Abstract: 1. Edaphic factors and initial conditions can regulate the speed of forest succession.Edaphic factors, which include soil chemistry and topography, determine soil resource availability and can filter species as forests mature. Initial plant cover early in succession can determine the rates at which secondary forests change in structure, richness, biomass and composition over time. While some of the effects of edaphic factors and initial conditions on forest succession have been studied, how they simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 108 publications
(163 reference statements)
3
32
1
Order By: Relevance
“…We found that lianas were increasing in our plots, but there was no support for the hypothesis that nutrient deposition contributes to observed liana increases. Our findings are consistent with observational studies (Dalling et al 2012, Ledo and Schnitzer 2014, Estrada‐Villegas et al 2020), which reported that soil nutrients and soil chemistry were poor predictors of liana abundance and distribution. Therefore, the distribution of lianas and their increase in neotropical forests are likely not the result of elevated nutrient deposition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that lianas were increasing in our plots, but there was no support for the hypothesis that nutrient deposition contributes to observed liana increases. Our findings are consistent with observational studies (Dalling et al 2012, Ledo and Schnitzer 2014, Estrada‐Villegas et al 2020), which reported that soil nutrients and soil chemistry were poor predictors of liana abundance and distribution. Therefore, the distribution of lianas and their increase in neotropical forests are likely not the result of elevated nutrient deposition.…”
Section: Discussionsupporting
confidence: 93%
“…In the same 50-ha plot, Ledo and Schnitzer (2014) reported that habitat type, which combined edaphic and topographical variables (e.g., elevation, slope, curvature, and aspect), did not explain liana distribution or abundance. Because lianas did not respond to aggressive nutrient addition in this study, and previous studies have not found a strong response of lianas to soil chemistry and habitat type (Dalling et al 2012, Estrada-Villegas et al 2020, it is unlikely that nutrient deposition is a strong explanatory factor for either the distribution of lianas or the increase of lianas in this and in other tropical forests with similar soil-nutrient levels.…”
Section: Nutrient Deposition Is An Unlikely Explanation For Increasincontrasting
confidence: 54%
See 1 more Smart Citation
“…A sizeable fraction of aboveground biomass is stored in trees outside forests (Graves et al 2018). Previous field work in our study region has demonstrated that fifteen‐years is a sufficient period of time to detect differences in metrics of succession between sites, including biomass accumulation and tree species richness (Estrada‐Villegas et al 2020).…”
Section: Methodsmentioning
confidence: 90%
“…Tropical forests restoration can significantly be influenced by the levels of changes in soil physicochemical property (Ehleringer & Sandquist, 2006; Estrada‐Villegas et al, 2019; Harcombe, 1980; Long et al, 2018) and arbuscular mycorrhizal fungi (AMF) (Asmelash et al, 2016; Neuenkamp et al, 2018) from the pre‐disturbance status. Hence, the soil physicochemical property and AMF resilience studies to forest degradation and deforestation are considered to be a crucial initial step in forest restoration planning (Ayala‐Orozco et al, 2018; Carrillo‐Saucedo & Gavito, 2020; Carrillo‐Saucedo et al, 2018; Safar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%